Returning Bulgarian Migrants: Status Inequalities and Social-Economic Mobility - Nonchev, Andrey; Hristova, Marieta (Research Papers, 2021)
The article explores the social inequalities and mobility of the returning Bulgarian migrants. Their socio-economic status and its transformations in the course of the migration movements are analyzed. The main focus is on economic (income, employment, property), educational and qualification inequalities between returning migrants. The vertical (ascending and descending) economic and social mobility of the remigrants throughout the migration cycle and its individual phases is also traced. Through self-assessments of the financial and social situation of the returning migrants, the complex stratification effects of the migration are presented.
Keywords: Mobility; Social stratification; Inequalities; Differentiation; Remigrants